Comparative Analysis of Anatomical Parameters of the Distal End of the Radius - Hussain Saheb Shaik; Indira Thatiparthi; N. Dhivya Dharshini; B. Sai Krishna Naik; J. K. Hari Haran; Pandit Vinodh Bandela (Current Medical Issues)
Background: The distal end of the radius is a critical anatomical structure involved in wrist biomechanics, and its morphometric characteristics are essential for clinical applications such as surgical planning, prosthetic design, and forensic identification. While previous studies have explored the morphometry of the radius, few have focused on bilateral comparisons of the distal end in paired specimens. This study aims to provide a detailed comparison of the morphometric parameters of the distal end of the right and left radii, assessing the degree of bilateral symmetry. Methodology: Eighteen paired radius specimens (right and left) were analyzed. Multiple morphometric parameters were measured, including length, weight, styloid process length, ulnar notch dimensions, and scaphoid and lunate facet diameters. Statistical analysis was performed using paired t-tests to compare the right and left sides, with a P < 0.0 considered statistically significant. Results: No statistically significant differences were observed between the right and left sides for any of the measured parameters (P > 0.0). The mean length of the right radius was 25.6 ± 1.5 cm, compared to 24.6 ± 1.6 cm on the left side (P = 0.2). The mean weight of the right radius was 37.7 ± 9.4 g, compared to 35.4 ± 7.9 g on the left side (P = 0.6). Similarly, no significant differences were found in the length of the styloid process, dimensions of the ulnar notch, or diameters of the scaphoid and lunate facets. The number of grooves, oblique grooves, and vertical grooves also showed no significant differences between the right and left sides. Conclusions: The findings of this study demonstrate a high degree of bilateral symmetry in the distal end of the radius, with no significant differences between the right and left sides for any of the measured parameters. These results suggest that side-specific considerations may not be necessary in certain clinical applications, such as surgical planning and prosthetic design.